Critical micelle concentration values for different surfactants measured with solid‐phase microextraction fibers. (17th June 2016) - Haftka, Joris J.‐H.; Scherpenisse, Peter; Oetter, Günter; Hodges, Geoff; Eadsforth, Charles V.; Kotthoff, Matthias; Hermens, Joop L.M.
Abstract: The amphiphilic nature of surfactants drives the formation of micelles at the critical micelle concentration (CMC). Solid‐phase microextraction (SPME) fibers were used in the present study to measure CMC values of 12 nonionic, anionic, cationic, and zwitterionic surfactants. The SPME‐derived CMC values were compared to values determined using a traditional surface tension method. At the CMC of a surfactant, a break in the relationship between the concentration in SPME fibers and the concentration in water is observed. The CMC values determined with SPME fibers deviated by less than a factor of 3 from values determined with a surface tension method for 7 out of 12 compounds. In addition, the fiber–water sorption isotherms gave information about the sorption mechanism to polyacrylate‐coated SPME fibers. A limitation of the SPME method is that CMCs for very hydrophobic cationic surfactants cannot be determined when the cation exchange capacity of the SPME fibers is lower than the CMC value. The advantage of the SPME method over other methods is that CMC values of individual compounds in a mixture can be determined with this method. However, CMC values may be affected by the presence of compounds with other chain lengths in the mixture because of possible mixed micelle formation. Environ Toxicol Chem 2016;35:2173–2181. © 2016 SETAC